Metal Complexes Diversity (MDPI - Multidisciplinary Digital Publishing Institute, 2026)
This Reprint showcases recent progress in the design, synthesis, and application of metal complexes, highlighting the remarkable diversity of their structures and functions. Metal complexes continue to attract significant scientific interest due to their central role in catalysis, materials science, and medicinal chemistry, as well as their potential to address current technological and biomedical challenges. The contributions collected in this Reprint demonstrate how controlled synthetic strategies and rational ligand design can fine-tune molecular architecture, electronic properties, and functional behaviour. The Reprint includes nine contributions comprising one authoritative review article and eight original research papers. Together, these works provide a broad and up-to-date overview of advances in coordination chemistry, with particular emphasis on conformational properties, reactivity, and biological activity. The featured studies address a wide range of metal centres and ligand systems, employing complementary experimental and theoretical approaches to explore structure–activity relationships, redox and electrochemical behaviour, and interactions with biologically relevant targets. By bringing together diverse perspectives and methodologies, this Reprint serves as a valuable reference for researchers seeking inspiration and insight into the development of next-generation metal-based catalysts, functional materials, and therapeutic agents.